Comparative effectiveness of Quizlet-based SDCL and Duolingo-based direct instruction on vocabulary mastery - Sutraeni Sutraeni; Sitti Asriati; Nur Qalby (English Learning Innovation, 2025)
This quasi-experimental study aimed to examine the effectiveness of technology-integrated instructional methods—Quizlet-based Self-Directed Collaborative Learning (SDCL) and Duolingo-based Direct Instruction (DI)—in enhancing vocabulary mastery among senior high school students in Indonesia. Twenty-seven students from SMA Muhammadiyah 6 Makassar were divided into two groups: an experimental group (n = 14) taught using SDCL and a control group (n = 13) taught using DI. Both groups completed vocabulary pre- and post-tests. Statistical analyses included normality testing, descriptive statistics, N-Gain Score analysis, and an independent samples t-test. The results showed that both instructional approaches improved vocabulary mastery, with mean post-test scores rising from 42.4 to 71.2 in the experimental group and from 32.1 to 65.4 in the control group. N-Gain analysis revealed slightly higher gains in the control group (M = 0.4839) compared to the experimental group (M = 0.4481). However, the independent samples t-test (p = 0.645) indicated no statistically significant difference in vocabulary improvement between the two groups. These findings suggest that both methods are effective and may be employed complementarily to support vocabulary learning in secondary education.